Topic Content:
- Factorization of Trinomials of the Form x² + bx + c
A trinomial is an algebraic expression containing three terms.
For example, ax2 + b + c is a trinomial because it has three terms i.e. ax2, bx, c when a = 1 this expression becomes x2 + b x + c, a simple trinomial.
Some quadratic expressions can be factorized by splitting the middle term.
Therefore, to factorize a trinomial of the form ax2 + bx + c, look for pairs of factors of the constant term c that add up to b i.e. the coefficient of x.
Worked Example 6.3.1:
Factorize:
a. x2 + 7x + 10
b. x2 + 3x + 2
c. x2 + 8x + 15
d. y2 + 9y + 18
e. 2x2 + 13x + 6
Solution
a. x2 + 7x + 10
i. First multiply The first and the last term i.e. a × c
ii. Look for the factors of 10x2, two factors when they are multiplied give 10x2 and when added they give 7x, which is the middle term.
Factors of 10: 1, 2, 5 and 10
Factors of 10x2 that add up to 7x are 2x and 5x
that is:
2x × 5x = 10x2
2x + 5x = 7x
⇒ \( \scriptsize 2x \: \times \: 5x = 10x^2 \)
⇒ \( \scriptsize 2x \: + \: 5x = 7x \)
So replace 7x with 2x + 5x
⇒ x2 + 2x + 5x + 10
Factorize by grouping
⇒ (x2 + 2x ) + (5x + 10)
⇒ x (x + 2 ) + 5 (x + 2)
= (x + 5 )(x + 2)
b. x2 + 3x + 2
Factors of 2: 1 and 2
∴ Factors of 2x2 that add up to 3x are 2x and 1x
So replace 3x with 2x + 1x
⇒ x2 + 2x + 1x + 2
Factorize by grouping
⇒ (x2 + 2x ) + (x + 2)
⇒ x(x + 2) + 1(x + 2)
= (x + 1)(x + 2)
c. x2 + 8x + 15
Factors of 15: 1, 3, 5 and 15.
⇒ x2 + 3x + 5x + 15
⇒ (x 2 + 3x) + (5x + 15)
⇒ x(x + 3) + 5(x + 3)
= (x + 5)(x + 3)
d. y2 + 9y + 18
Factors of 18: 1, 2, 3, 6, 9 and 18
⇒ y2 + 3y + 6y + 18
⇒ (y2 + 3y) + (6y + 18)
⇒ y (y + 3) + 6(y + 3)
= (y + 6)( y + 3)
e. 2x2 + 13x + 6
Factors of 6: 1, 2, 3, 4, 6, and 12.
⇒ 2x2 + 12x + x + 6
⇒ (2x2 + 12x ) + (x + 6)
⇒ 2x (x + 6) + 1(x + 6)
= (2x + 1)(x + 6)
Worked Example 6.3.2:
Factorize:
i. 4x2 – 3x – 22
ii. 2e2 – 3e + 1
Solution
i. 4x2 – 3x – 22
Factors of 88: 1, 2, 4, 8, 11, 22, 44, and 88
+ 8x – 11x = -3x or -11x + 8x = -3x
⇒ 4x2 + 8x – 11x – 22
⇒ (4x2 + 8x ) – (11x + 2)
⇒ 4x (x + 2) – 11 (x + 2)
= (4x – 11) (x + 2)
ii. 2e2 – 3e + 1
⇒ 2e2 – e – 2e + 1
⇒ (2e2 – e) – (2e – 1)
⇒ e(2e – 1) – 1(2e – 1)
= (e – 1)(2e – 1)